Penatalaksanaan Fisioterapi Pada Kondisi Tennis Elbow Dextra Di Rsud Dr. Moewardi Surakarta - Adityawarman, Arga Maulana, Sugiono, S.Fis.MH.Kes (2015)
Background: Tennis Elbow is a disorder of the muscles around the elbow jointdue to damage to the muscle origo extensor carpi radialis longus and brevis. Physiotherapy is a form of health care that is addressed to an individual or groups for caring and restoring motion throughout the lifecycle of bodily functions using manual handling or equipment. Objective: To determine TENS in relieving pain in tennis elbow condition? To know Exercise therapy in improving nuscle strength on condition of tennis elbow? Results: After 6 times therapy with TENS modalities and exercise therapy showed a reduction in pain. Silent pain before and after theraphy 1, tenderness T1 is 3, T6 is 2. Paint elbow flexion-extension T1 is 4, T6 is 3, pain dorsal flexion motion T1 is 4, T6 is 3, pain palmar flexion mountain T1 is 3, T6 is 3, paint supination T1 is 3, T6 is 2, paint pronation monition T1 is 4, T6 is 5. An increase muscle strength wrist flexion muscle strength T1 is 5, T6 is 5. T1 wrist extensor muscle strength is 4, T6 is 5 Methods: the management of physiotherapy in the condition of tennis elbow dextra using TENS and Exercise therapy. Conclusion: TENS can reduce pain and exercise therapy can improve muscle strength in tennis elbow dextra condition. Suggestion : Be serious in exercising and wear Decker, to physiotherapy in doing ministry should conduct a thorugh and systematic examination.